High Serum Serotonin Predicts Increased Risk for Hip Fracture and Nonvertebral Osteoporotic Fractures: The MrOS Sweden Study. (11th May 2018) - Kristjansdottir, Hallgerdur Lind; Lewerin, Catharina; Lerner, Ulf H; Waern, Ewa; Johansson, Helena; Sundh, Daniel; Karlsson, Magnus; Cummings, Steve R; Zetterberg, Henrik; Lorentzon, Mattias; Ohlsson, Claes; Mellström, Dan
ABSTRACT: Because several studies have implicated serotonin as a regulator of bone mass, we here explore its potential association on fracture risk and falls, as on bone mineral density (BMD) and muscle strength, in humans. Serum levels of serotonin were analyzed in 950 men (aged 69 to 81 years), participating in the Gothenburg part of the population‐based study MrOS Sweden. Men taking selective serotonin reuptake inhibitors (SSRIs) had a mean value of 31.2 μg/L compared with 159.4 μg/L in those not taking SSRIs. SSRI users were excluded from further analysis. During 10‐year follow‐up, 224 men exhibited fractures, including 97 nonvertebral osteoporotic fractures (57 hip fractures), and 86 vertebral fractures. Serotonin was associated with hip fracture in linear analysis (hazard ratio [HR] = 1.27, 95% confidence interval [CI] 1.03–1.58) and to all fractures in a nonlinear manner, when quintiles of serotonin was included in quadratic terms (HR = 1.12, 95% CI 1.04–1.21). Men in serotonin quintile 5 had, in multivariable analysis, a HR of 2.30 (95% CI 1.31–4.02) for hip fracture and 1.82 (95% CI 1.17–2.85) for nonvertebral fractures compared with men in quintiles 1 to 4. Men in quintile 1 had, in multivariable analysis, a HR of 1.76 (95% CI 1.03–2.99) for nonvertebral fractures compared with men in quintiles 2 to 4. No association was found with vertebral fractures. Individuals in serotonin quintile 1 had higher prevalence of falls compared with quintiles 2 to 5 (odds ratio = 1.90, 95% CI 1.26–2.87). Serotonin was positively associated with hand‐grip strength (r = 0.08, p = 0.02) and inversely with hip BMD (r = −0.10, p = 0.003). To assess the association between SSRIs and falls and fractures, the total MrOS Sweden cohort was examined ( n = 3014). SSRI users ( n = 90) had increased prevalence of falls (16% versus 33%, p = 0.0001) and increased rate of incident fractures (28.0 versus 44.7 per 1000 person‐years, p = 0.018). We present novel data showing that high levels of serotonin predict an increased risk for hip fracture and nonvertebral osteoporotic fractures. © 2018 American Society for Bone and Mineral Research.